STUDI KOMPARATIF PENGUKURAN KEKASARAN JALAN (INTERNATIONAL ROUGHNESS INDEX/IRI) MENGGUNAKAN KENDARAAN RODA DUA DAN RODA EMPAT - Rendy Dwi Pangesti; Delila Jelita Ayu; Belifa Rahma Putri (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
Uneven road surface conditions affect the comfort and performance of transportation services, requiring objective measurements using the International Roughness Index (IRI). The development of smartphone-based applications allows IRI measurements to be carried out with various vehicles, but the influence of vehicle type on measurement results remains understudied. This study aims to compare the IRI values generated by two-wheeled and four-wheeled vehicles on the same road section and identify the level of difference. The study used a field survey method on road sections in Tembalang District, Semarang City. Measurements were conducted using the RoadLab Pro application installed on a smartphone. The data were then analyzed descriptively and tested using a paired t-test at a significance level of 5%. The results showed an average IRI of two-wheeled vehicles of 3,237 m/km and four-wheeled vehicles of 4,253 m/km. The statistical test produced a p value <0.05, indicating a significant difference. However, a correlation of 0.668 indicates a consistent pattern of change between road sections. This study confirms that vehicle type influences IRI values and requires adjustments to ensure consistent comparison of measurement results.